2015
DOI: 10.4067/s0717-95022015000300010
|View full text |Cite
|
Sign up to set email alerts
|

A Communicating Branch between the Dorsal and Superficial Ramus of the Ulnar Nerve (Kaplan's Anastomosis): Clinical and Surgery Discussion

Abstract: SUMMARY:The Kaplan´s anastomosis represents the communication between the dorsal and superficial branch of the ulnar nerve distal to ulnar canal. In the present study, a case about this nerve communication, found in a male adult cadaver, is reported. Information about brachial plexus distal anastomosis is fundamental for interpretation of clinical and electrophysiological findings, in order to establish the precise diagnosis of neurological lesions at this level. Its relations with flexor carpi ulnaris muscle'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
2
1
2
Order By: Relevance
“…8 However, there are variations of this anastomosis such as the atypical connection of the dorsal branch to the deep branch of the ulnar nerve as described by Ghabriel and Makar. 9 In this study, the anastomosis occurred between the medial division of the dorsal branch of the ulnar nerve at a midpoint between the origins of the superficial and deep branches, a finding that differs from those of Paraskevas et al 6 and Torre et al, 7 in which both studies reported anastomosis of the dorsal branch of the ulnar nerve to the ulnar nerve proximal to the emissions of the superficial and deep branches. In addition, the anastomotic medial division did not suppress the cutaneous aspect of the medial margin of the hand in direction of the dorsal face, which differs from previous papers.…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…8 However, there are variations of this anastomosis such as the atypical connection of the dorsal branch to the deep branch of the ulnar nerve as described by Ghabriel and Makar. 9 In this study, the anastomosis occurred between the medial division of the dorsal branch of the ulnar nerve at a midpoint between the origins of the superficial and deep branches, a finding that differs from those of Paraskevas et al 6 and Torre et al, 7 in which both studies reported anastomosis of the dorsal branch of the ulnar nerve to the ulnar nerve proximal to the emissions of the superficial and deep branches. In addition, the anastomotic medial division did not suppress the cutaneous aspect of the medial margin of the hand in direction of the dorsal face, which differs from previous papers.…”
Section: Discussioncontrasting
confidence: 51%
“…8 No entanto, existem variações desta anastomose, como a conexão atípica do ramo dorsal ao ramo profundo do nervo ulnar conforme descrito por Ghabriel e Makar. 9 Neste estudo, a anastomose ocorreu entre a divisão medial do ramo dorsal do nervo ulnar no ponto médio entre as origens dos ramos superficial e profundo, achado que difere daqueles de Paraskevas et al 6 e Torre et al, 7 uma vez que ambos estudos relataram anastomose do ramo dorsal do nervo ulnar ao nervo ulnar proximal às emissões dos ramos superficial e profundo. Além disso, a divisão medial anastomótica não suprimiu o aspecto cutâneo da margem medial da mão em direção à face dorsal, o que difere de trabalhos anteriores.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Kaplan's anastomosis provides sensory innervation to this region, with variations on the nervous distribution pattern. It accounts for the pain and loss of sensitivity in patients undergoing hand surgery due to damage to the pisiform bone, the flexor carpi ulnaris tendon, or damage to the Guyon canal (Torre et al, 2015).…”
Section: Introductionmentioning
confidence: 99%